2019
DOI: 10.1002/hep.30301
|View full text |Cite
|
Sign up to set email alerts
|

LXRα Promotes Hepatosteatosis in Part Through Activation of MicroRNA‐378 Transcription and Inhibition of Ppargc1β Expression

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a major risk factor of many end‐stage liver diseases. Alterations in microRNA expression have been reported in patients with NAFLD. However, the transcriptional mechanism(s) of dysregulated microRNAs under the state of NAFLD is poorly described, and microRNAs that regulate the pathogenesis of NAFLD synergistically with their regulators remain unknown. Here we report that microRNA‐378 expression is significantly increased in fatty livers of mice and patients with NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
(76 reference statements)
2
21
0
Order By: Relevance
“…The two mature strands, miR-378a-3p and miR-378a-5p, originate from the first intron of the peroxisome proliferator-activated receptor gamma, coactivator 1 beta (ppargc1b) gene encoding PGC-1β 12 , 13 . Different from other miRNAs, miR-378 possesses its own transcription machinery independent of its host gene 14 . A previous study combining database mining, EST extension, and 5′RACE and 3′RACE confirmed that the nuclear receptor Liver X receptor alpha (LXRα) is a transcription factor that regulates miR-378 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two mature strands, miR-378a-3p and miR-378a-5p, originate from the first intron of the peroxisome proliferator-activated receptor gamma, coactivator 1 beta (ppargc1b) gene encoding PGC-1β 12 , 13 . Different from other miRNAs, miR-378 possesses its own transcription machinery independent of its host gene 14 . A previous study combining database mining, EST extension, and 5′RACE and 3′RACE confirmed that the nuclear receptor Liver X receptor alpha (LXRα) is a transcription factor that regulates miR-378 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Different from other miRNAs, miR-378 possesses its own transcription machinery independent of its host gene 14 . A previous study combining database mining, EST extension, and 5′RACE and 3′RACE confirmed that the nuclear receptor Liver X receptor alpha (LXRα) is a transcription factor that regulates miR-378 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of miRNAs is controlled by its own promoter sequence that can be bound and regulated by transcription factors. For instance, the transcription factor LXRα was proved to activate miR-378 expression by bind to its promoter region [47] and MYC could recruited DNMT3A to the promoter region of miR-200b and repress its expression [48]. In this study, we found that pluripotent factors SOX2 and ESRRB could promote miR-1343 activation, but did not affect the activity of miR-545.…”
Section: Discussionmentioning
confidence: 57%
“…MiRNA has been implicated as a crucial regulator in metabolic diseases by silencing genes at the posttranscriptional level. Growing evidence demonstrated that a large number of miRNAs, such as miR-122, miR-378 and miR-34a, are involved in the pathogenesis of NAFLD [30,31]. However, whether miRNAs are involved in the uric acid-induced hepatocytes lipid accumulation is unclear.…”
Section: Discussionmentioning
confidence: 99%